Association between multiple meteorological variables and seasonal influenza A and B virus transmission in Macau. Issue 11 (November 2022) - Ng, HoiMan; Li, Yusi; Zhang, Teng; Lu, Yiping; Wong, ChioHang; Ni, Jinliang; Zhao, Qi
Abstract: Few studies have evaluated the influence of meteorological variables on different influenza types in subtropical regions. This study aimed to explore the association between meteorological variables and the onset of influenza A (Flu-A) and B (Flu-B) in Macau. Daily influenza case data in Macau were collected from Kiang Wu Hospital from 1 January, 2014 to 31 December, 2018. Daily meteorological data were obtained from the Macau Meteorological Service. The distributed lag non-linear model (DLNM) was used to estimate the effects of meteorological variables on seasonal influenza outbreaks. Regarding mean air temperature (temp), the peaks of the cumulative relative risks (RRs) of Flu-A and Flu-B were both at 4.0 °C and 28.0 °C. Regarding the diurnal temperature range (DTR), the peaks of the cumulative RR of Flu-A were at 1.0 °C and 5.0 °C, while the cumulative RR of Flu-B increased as the DTR decreased. The association between influenza risks and relative humidity (RH) showed a U-shape curve. The risk of influenza increased when the RH was below 50% or above 90%. The risk of both types of influenza increased significantly when the sunshine duration (SD) was below 3.5 h. Taking the median value as the reference, a significant cold effect was observed over 16–24 days lag for Flu-A. Lag effects were found for both types of influenza in low-DTR, and humid and short SD conditions. This study revealed complex non-linear association between meteorological variables and the different influenza types in Macau. Abstract : Distributed lag non-linear model, Seasonal influenza, Meteorological variables.